Serum Lipid Profile in Iraqi patients with Breast Cancer - Al-Rubaye, Faisal Gh.; Morad, Taha Shawi; Hamzah, Mohammed I.; Hasan, Shatha M. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Breast cancer (BC) is a type of cancer originating from breast tissue, Lipid profile seems to influence the development of female breast cancer, especially in the presence of an increased body mass index so. Objective: to explore the status of lipid profile in women with breast cancer. Subjects and methods: the present study is a cross-sectional study (2010/2011) done at Al-Yarmouk Teaching Hospital. Includes measurement of LP in sera of postmenapausal newly diagnosed women with BC in comparison with healthy control women. This measurement was done using colorimetric method. In The results of this study include a total of 100 patients with BC were involved in this study, they were classified as newly diagnosed postmenopausal women with BC G1: (n=100); together with 100 healthy Postmenopausal women as a control group G2: (n=100). Results: Serum LP was significantly altered in newly diagnosed BC groups whom receive no therapy (G1) [P < 0.001] when compared with control group (G2): this alteration was in term of significant increment in TC, TG, LDL and VLDL accompanied by elevation of HDL which was significant [P < 0.05] Conclusion: level of LP was significantly elevated in BC group suggesting atherosclerosis.